Management styles in small and medium-sized enterprises in Malaysia: A recent survey - Noor Syakirah Zakaria; Mohd Khairuddin Hashim (Penerbit UMS, 2017)
Management styles have received much attention as a field of study as well as practice. However, as an area of research, the literature review reveals that limited studies have attempted to investigate the management styles embraced by small and medium-sized enterprises (SMEs), especially in the Malaysian context. This study attempted to address this research issue. Data for the study was collected from 186 SMEs operating in the manufacturing sector by using structured questionnaires. The analyzed data gathered from the SMEs suggest that these firms adopted five styles of management. Among the management styles identified in the study includes; autocratic, participative, nurturance task, paternalistic and laissez-faire.